Occupational exposure to metals and PAHs: combining literature-based exposure and in vitro hazard data towards a mixture risk assessment a mixture risk assessment - Tavares, Ana Maria (2022)
Abstract publicado em: Toxicol Lett. 2021 Sep;350(Suppl.):S210 (P21-14). https://doi.org/10.1016/S0378-4274(21)00729-3